RETRACTED: Social effect of the protective fabrics on human health and environment - Turaxujayeva Nilufar; Yermatov Rustam; Mamashoyev Fazliddin; Abdurakhimova Maftunakhon; Khankhadjaeva Nilufar (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001